Level of Knowledge of Pregnant Women Anemia Working In the Health Mrican Kediri - Luqmanasari, Endah (Universitas STRADA Indonesia, 2017)
The gestation period is a period where the body craves maximum intake of good eating Pregnant women often complain usually frequent fatigue, dizziness, shortness of breath, pale face and a wide range of other complaints. All of these complaints is an indication that the pregnant women are suffering from anemia during pregnancy. A state of the decreasing levels of hemoglobin, hematocrit, and erythrocyte below normal value. The purpose of this study is the knowledge level of anemia in pregnant women PHC Mrican Kediri. The design / design of this study is a qualitative descriptive study conducted on May 9-14, 2014. The study population of pregnant women at health centers 81 Mrican Kediri. This study using purposive sampling and obtained a sample of 55 respondents pregnant women. Retrieving data using questionnaires. Data processing includes editing, coding, scoring, tabulating and analyzed. The study, of 55 respondents about their level of knowledge about anemia of pregnant women in the realm know (C1) mostly quite as many as 31 respondents (56.4%) and understanding (C2) quite as many as 31 respondents (56.4%), as well as applied (C3) are largely quite as many as 32 respondents (58.2%). Based on the results of this study concluded that the level of knowledge of pregnant women about the anemia is enough. Therefore, the midwife should give a clearer counseling to pregnant women in order to understand more about anemia. Besides that, as an input to further improve services to pregnant women by providing information about the IEC or anemia